Evidence-based clinical practice manual: Cardiopulmonary-cerebral resuscitation - Navarro Vargas, José Ricardo; Matiz-Camacho, Hernando; Osorio-Esquivel, Javier (Colombian Journal of Anesthesiology, 2015)
Cardio respiratory arrest in adults arises as a consequence of coronary artery disease inmore than 60% of cases. At present, it is considered a public health problem. It is important to keep in mind that prevention, through the adoption of healthy habits, isthe principle contributor to the reduction of morbimortality. Nevertheless, when a malignarrhythmia that leads to cardiac arrest presents itself, the outcomes are directly related tothe speed and quality with which cardiopulmonary resuscitation maneuvers are put intoeffect, and to the integral management of the clinical condition that is post-cardiac arrestsyndrome.These clinical practice handbook aim to provide sufficient information in order to guarantee appropriate medical attention in these cases. It is based on international norms ofthe lex artis in terms of the understanding and management of cardiac arrest. What's more, criteria for determining brain death, and the organization of the advancedresuscitation team, which goes by various names around the world, emergency medicalsystem, code blue, mega code, advanced resuscitation code, are included here.